Comparison study of results of vitrectomy and vitrectomy with scleral buckling for the treatment of patients with rhegmatogenous retinal detachment at high risk proliferative vitreoretinopathy (Ukrainian Journal of Ophthalmology, 2026)
The aim of our study was to analyze the effectiveness of vitrectomy and vitrectomy with scleral buckling in patients with a high risk of proliferative vitreoretinopathy.Material and Methods: Of the 367 patients (394 eyes) who applied in 2011-2014, in the National Center for Ophthalmology named after acad. Zarifa Aliyeva with diagnosis of primary rhegmatogenous retinal detachment (RRD) we selected 217 patients (231 eyes) with a high risk of proliferative vitreoretinopathy. The patients were considered to be of a high risk of  proliferative vitreoretinopathy (PVR) development if they had RRD in three or more quadrants, more than one hour retinal breaks, pre-operative PRV, vitreous hemorrhage, aphakia/ pseudophakia, choroidal detachment. Vitrectomy and vitrectomy with scleral buckling were performed in 133 eyes (57.6% of cases) and 98 eyes (42.4% of cases), respectively.Results: The primary anatomical success of the surgery was noted in 71.4 and  70.4% of cases after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.866. The final anatomical success was observed in 88.7 and 92.9%, after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.290. In pseudophakia the primary anatomical effect was noted in 80.6 and 53.3% of cases after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.054. In RRD associated with lowere breaks, the final anatomic success was observed in 85% and 96.2% of cases after vitrectomy and vitrectomy with scleral buckling, respectively, p=0.05.Conclusion: In rhegmatogenous retinal detachments in patients with a high risk of developing proliferative vitreoretinopathy, vitrectomy is more effective in pseudophakic patients and vitrectomy with scleral buckling is more effective in retinal detachments caused by inferior breaks.
Keywords: Rhegmatogenous retinal detachment; pars plana vitrectomy; scleral buckling; proliferative vitreoretinopathy